Pengembangan Perangkat Pembelajaran Pendidikan Agama Kristen Dengan Model Quantum Teaching Tipe Tandur Berbantuan Multimedia Presentasi - Bekata, Halena Muna (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
This research is oriented towards PAK learning using the quantum teaching model, tandur type assisted by multimedia presentations in class VIII. The aim of the research is to produce a PAK learning device with a tandur-type quantum teaching model assisted by multimedia presentations that is valid, knowing the practicality and effectiveness of the device. R&D method with Borg & Gall procedures. Research products include Syllabus, RPP, BPD, LKPD, TKPM, and multimedia presentations. The research variables are validator responses to device documents, student responses, teacher observations of learning management, observations of character responsibility and problemsolving skills as well as problem solving ability tests. This research was implemented at Gideon Alor Christian Middle School, Semarang. The subjects of device validation are experts, the research subjects are students and teachers. This research data processing uses descriptive analysis, t-comparison test and regression influence test. The results of the research show: (1) the validity of the device is in the very valid category (2) the practicality of the device is in the very practical category (3) the effectiveness of learning is demonstrated through: (a) students complete the TKPM, (b) comparison test of class TKPM scores the experiment is better than the control class (c) the character of responsibility and problem solving skills have a positive effect on problem solving abilities.